Módní oděv jako paradigmatický model posthumanismu: teorie a praxe - Muchová, Linda (Filosoﬁcký časopis)
The study focuses on the theoretical articulation of the points of departure and assumptions of the so-called posthumanist turn in fashion design. In the first phase, we address the connection between fashion and modernity, which leads us to inquire about what posthumanist clothing fashion might have to say about the nature of modernity. In the ensuing discussion about the anthropology of clothing and the thinking of corporeality, we will point to a transformed understanding of the relationship between culture and nature, which questions the premises of classical, “humanistic” modernity. According to this concept, nature does not stand in opposition to culture and politics, it is not the past of the human race from which it should be emancipated. Nature as a utopia or a means of liberating humankind is placed in the same position as technology has been occupying. In the fourth, and final, section, we present an annotated sample of contemporary fashion theory, practice and creation in the narrow sense of the word. The productions of Iris van Herpen, Hussein Chalayan and Gareth Pugh vividly illustrate the posthumanist strategies in which human existence finds its realization in a close connection with the elements, technology and organic nature.